Improved FNA cytology results with a near patient diagnosis service for non-breast lesions. Issue 7 (July 1998) - Mayall, F; Denford, A; Chang, B; Darlington, A
Abstract : AIM: To review fine needle aspiration (FNA) cytology from sites other than the breast a year before and a year after the introduction of a near patient FNA diagnosis (NPFD) service in which the FNA were performed by a pathologist and reported within a few minutes. METHODS: The setting was a large hospital in rural New Zealand. The year before the introduction of the NPFD service was examined retrospectively, and the year after prospectively. The pattern of use and the quality of the results before and after starting the NPFD service were compared. RESULTS: Time taken to report the specimens decreased from a few days to a few minutes. There were statistically significant changes in the following: an increase from 237 to 304 in the number of non-breast FNA performed, and in particular an increase from 65 to 113 in the number for general surgery; an increase in the use of immunolabelled flow cytometry from 0 to 19 and cell blocks from 3 to 41; an increase in specificity from 53% to 80%; a decrease in the overall inadequacy rate from 29% to 9%; and a decrease in the inadequacy rate for cancers from 9% to 2%. The cost of the non-breast FNA service increased by about 9200 Pounds a year. CONCLUSIONS: Starting an NPFD service for sites other than the breast greatly reduced the reporting time and produced statistically significant increases in the use of FNA cytology and in the quality of the results.